2013
DOI: 10.1117/12.2003697
|View full text |Cite
|
Sign up to set email alerts
|

A novel pixel design with hybrid type isolation scheme for low dark current in CMOS image sensor

Abstract: New isolation scheme for CMOS image sensor pixel is proposed and its improved dark current performance is reported. It is well known that shallow trench isolation (STI) is one of major sources of dark current in imager pixel due to the existence of interfacial defects at STI/Si interface. On the account STI-free structure over the whole pixel area was previously reported for reducing dark current. As the size of pixel pitch is shrunk, however, it becomes increasingly difficult to isolate in-pixel transistors e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Techniques like ring-gate shared pixel design enclosed by p-type layers, have also been proposed [10]. Choi et al have suggested a hybrid STI/p-well isolation scheme to achieve low leakage [23], which was benchmarked against the STI and the pure p-well isolation techniques. However, the pure p-well isolation was achieved with high spacing leading to low fill factor (FF) and the hybrid-p-well isolation was compared to the STI isolation by keeping a similar FF.…”
Section: Introductionmentioning
confidence: 99%
“…Techniques like ring-gate shared pixel design enclosed by p-type layers, have also been proposed [10]. Choi et al have suggested a hybrid STI/p-well isolation scheme to achieve low leakage [23], which was benchmarked against the STI and the pure p-well isolation techniques. However, the pure p-well isolation was achieved with high spacing leading to low fill factor (FF) and the hybrid-p-well isolation was compared to the STI isolation by keeping a similar FF.…”
Section: Introductionmentioning
confidence: 99%